SHALAHUDDIN AL-’AḌLABI Analisis Metodologi Kritik Matan Hadīṡ Terhadap Riwayat Yang Bertentangan Dengan Akal, Indra dan Sejarah - Muhammad Nabat Ardli; Reza Hilmy Luayyin (Al-Bukhari : Jurnal Ilmu Hadis, 2024)
Research on Hadīṡ cannot be separated from two main elements, called sanad and matan. Among Hadīṡ scholars, research on sanad receives more attention than matan, which prompted Salahuddin al-’Aḍlabi to write the book "Manhaj Naqd al-Matn 'Ind Ulama al-Hadits al-Nabawi”, which specifically discusses the critique of Hadīṡ texts. Among several of his critical methodologies are critiques of the matan through rational, sensory, and historical approaches. This research uses descriptive analysis with a normative approach. The results of the analysis show that 1) Al-’Aḍlabi's critical methodology towards Hadīṡ texts that contradict Reason, Senses, and History employs several methods and approaches including hierarchical and integrative assumptions, as well as synchronization methods. 2) Some of Al-’Aḍlabi's assumptions employ a hierarchical approach, where each assumption cannot be separated from the Qur'an and Hadīṡ, reason, then senses, and followed by history. The hierarchical assumptions made can be done not necessarily in a structured (systematic) way but can be done randomly as long as the Qur'an and Hadīṡ remain the top priority in building assumptions. Al-’Aḍlabi's assumptions also use an integrative approach where his assumptions are built and mutually supported among various elements to produce a higher norm. 3) A variety of methods employed by Al-’Aḍlabi with rational, sensory, and historical approaches use synchronization methods. The synchronization method referred to is when there is a contradiction in understanding the Hadīṡ text.